WAHYU DAN KEBERHASILAN DAKWAH MUHAMMAD (Sebuah Kajian Sosiologis) - Khadiq Khadiq (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2007)
Islam is embraced by many people through a relatively fast spread. This fact cannot be separated firom the role of its preacher, Muhammad. His success in da’wa activities was contributed by his social roles as well as the revelation that he brought. This article tries to explain that both the revelation and the social factors greatly supported his da’wa. Beside his positives, the existence of Quran as a revelation contributed the social legitimacy that Muhammad was considered as a figure to be followed in spite of his contrary values to the cultures of his time.